Synthesis, characterization and biological activities of cetirizine analogues. Issue 4 (2011) - Sultana, Najma; Arayne, M. Saeed; Shamshad, Hina; Mirza, Agha Zeeshan; Naz, Malik Asia; Fatima, Beenish; Asif, M.; Mesaik, M. Ahmed
Abstract : Cetirizine second generation H1 -receptor antagonist is an acid metabolite of hydroxyzine. Present work was based on six new analogues of cetirizine having nucleophilic substitution reaction synthetic pathway. The reactions were proceeded by replacing the scaffold on the cetirizine moiety using nucleophilic substitution reaction. The structures of analogues were confirmed using UV, IR, 1 H NMR and mass spectroscopic techniques. The analogues were tested for the anti-inflammatory activities on cellular immune response. Oxidative burst response of phagocytes after exposure to the analogues was found to exhibit moderate to significant inhibitory activity (23 to <3.1). However, the compounds as MPC and PPC also showed remarkable inhibitory effect on PHA activated T-cells response and may prove to be lead compounds in therapeutic world.